Social justice, corporate social responsibility and sustainable development in South Africa - Anwana, Emem (HTS teologiese studies, 2020)
South Africa is a country that is still in the transitioning process of providing an equal, equitable and just society for its previously disadvantaged people. The country faces several socio-economic developmental challenges, ranging from inadequate housing, high crime rates, violence against women and children, ineffectual health facilities, a slowing economy and high youth unemployment, which invariably affect the business community. If South Africa is to achieve sustainable economic transformation, the business community along with other stakeholders must participate in ensuring social justice and socio-economic development for its previously disadvantaged people. This article contributed to the discourse on the assertion that social justice and socio-economic development are central for sustainable development in any society. The article called for the assistance and participation of other stakeholders, particularly the business community, to help build a just, healthy and robust environment, which translates into a strong community and portends a sustainable environment for businesses.Contribution: This article assessed the effectiveness of legislating social justice and corporate social responsibility. The article adopted the European Union’s Better Regulation evaluation methods to evaluate the effectiveness of the country’s social justice and corporate social responsibility legislation and the influence of the legislations on the socio-economic developmental challenges affecting the country.